Polysaccharide Peptide Extract From Coriolus versicolor Increased Tmax of Tamoxifen and Maintained Biochemical Serum Parameters, With No Change in the Metabolism of Tamoxifen in the Rat - Razmovski-Naumovski, Valentina; Kimble, Benjamin; Laurenti, Daunia; Nammi, Srinivas; Norimoto, Hisayoshi; Chan, Kelvin (Frontiers in Pharmacology, 2022)
Background: Polysaccharide peptide (PSP) extract of Coriolus versicolor (L.) Quél. (1886) (Trametes; Polyporaceae) is increasingly used in cancer to support the immune system. However, its interaction with tamoxifen is unknown. Aim of the study: To investigate the effect of a PSP extract on the pharmacokinetics, biochemical parameters and depletion of tamoxifen. Methods: The pharmacokinetic and biochemical parameters of tamoxifen (20 mg/mL oral single dose and repeated dosing for 13 days) was investigated in female Sprague Dawley rats with or without PSP (340 mg/kg orally for seven days) (n=5 per group). Tamoxifen (5 µM) depletion rate with PSP (10 -100 µg/mL) was measured in female rat hepatic microsomes in vitro. Results: Compared to tamoxifen alone, the time to reach maximum concentration (Tmax) significantly increased by 228% (4.15 ± 1.15 versus 13.6 ± 2.71 h) in the single tamoxifen dose with PSP and 93% (6 ± 2.17 versus 11.6 ± 0.4 h) in the repeated tamoxifen dosing with PSP (p < 0.05). No significant changes in the area-under-curve and maximum concentration were observed in the single dose and repeated tamoxifen dosing plus PSP compared to tamoxifen alone. Pharmacodynamically, the repeated tamoxifen dosing with PSP maintained 19 out of 23 hepatic, renal and cardiac biochemical serum parameters in rats compared to untreated rats (p > 0.05). PSP extract did not significantly alter in vitro intrinsic clearance of tamoxifen compared to tamoxifen control. Conclusion: With the increased use of PSP as an adjunct therapy, this study highlights the importance of clinician’s knowledge of its interaction with tamoxifen to avoid compromising clinical actions and enhancing clinical therapy.